Infectious diseases and antimicrobial prescribing: Online spaced education for junior doctors. (September 2020) - Menon, V.; Chubaty, A.; Clezy, K.; Su, Y.; Post, J.J.; Janssen, A.; Shaw, T.; Konecny, P.
Highlights: The known: Inappropriate antimicrobial prescribing, a promoter of antimicrobial resistance, remains problematic. Junior doctor training in infectious diseases and antimicrobial prescribing is suboptimal. The new: Online spaced education with gamification improves prescriber knowledge, is feasible and acceptable to junior doctors. The implications: Application of this novel technology to continuing medical education in infectious diseases has potential to improve antimicrobial prescribing, clinical outcomes and mitigation of antimicrobial resistance, and as such warrants further study. Abstract: Background: Inappropriate antimicrobial prescribing may harm patients and drive antimicrobial resistance. Junior doctors' knowledge of infectious diseases and antimicrobial prescribing is inadequate. Online spaced case-based learning can improve knowledge. Objective: To develop infectious diseases and antimicrobial prescribing course content for online spaced education and assess its effectiveness and feasibility for junior doctors. Methods: Infectious diseases and antimicrobial course content was developed for an online spaced education platform (Qstream Inc., Burlington, MA). Junior doctors (postgraduate years 1–3) at two tertiary teaching hospitals in Sydney participated in the study. Course content was provided with Qstream at one hospital and at the other hospital via two face-to-face (FTF) tutorials from August to October 2017. Knowledge and self-confidence were compared before and after training within and between both cohorts. Results: Participation in the course was higher in the Qstream cohort with 48/127 (37.8%) completing the course compared with 44/110 (40%) attending one or both FTF sessions, of whom 22/110 (20%) attended both. Improvement in mean knowledge score from 69.7% to 81.5% in the Qstream cohort was significantly greater than the FTF cohort's minimal improvement from 67.6% to 67.9% (95% CI 2.79–20.33; P = 0.01). In the Qstream cohort mean confidence rating (0–10) improvement from 5.14 to 6.55 was greater than the FTF group improvement from 5.37 to 5.85 (95% CI 0.132–1.171; P = 0.02). Qstream feedback was very positive. Conclusions: Online spaced education in infectious diseases and antimicrobial prescribing was feasible, acceptable and effective for junior doctors. It has potential to reduce inappropriate antimicrobial prescribing and warrants further investigation.